Percutaneous Nephrolithotomy: A Comparison of Tubeless versus the Standard technique - Zein El Amir, Muhammad Ali Shahiman, Zeeshan Qadeer, Rameez Ahmed Mughal, Ashfaq Ali, Zein El Amir, Muhammad Ali Shahiman, Zeeshan Qadeer, Rameez Ahmed Mughal, Ashfaq Ali (Journal of Rawalpindi Medical College, 2021)
Objective: The proposed study aimed to assess the utility of tubeless PCNL in terms of efficacy and safety when compared with the standard tubed PCNL. Materials & Methods: In this study 280 patients (age ranged 08-70 years) who underwent PCNL were included. Results: The patients were from both genders i.e., 156 males and 124 females. Out of 280 patients, 140 had a 16 FR nephrostomy tube (Group A) whiles an equal number had 4.8F DJ Stent (Group B) for postoperative drainage. A comparison of the postoperative outcome among the two groups was made for a period of two years (November 2017 to October 2019). Neither any significant difference was found in the mean stone size, operative time, nor was stone-free status, nor any major complication observed. The mean hospital stay for group A and group B was 4.5 days (range 3 to 6) and 3.2 days (range 2 to 4) respectively. An early postoperative wound soakage was found in 18 (12.8%) cases of group A in contrast to the group B patients in whom only 2 (1.4%) had soakage. Conclusion: It was concluded that Tubeless PCNL as compared to the standard tubed PCNL was found more efficacious and safer and it should be adopted as a routine procedure.